Research and practice of POTN equipment modeling method based on transporrt API - Ruiquan JING; Qian HU; Guoyong ZHAO (Dianxin kexue)
How to control packet enhanced OTN (POTN)equipment by using hierarchical SDN controllers is the research focus of the transport SDN, which involves reasonable modeling of POTN equipments. Firstly, the status of POTN equipment modeling method based on transport API was analyzed. Then a modeling method for centralized switching POTN equipment was proposed. During OIF/ONF 2016 global transport SDN prototype demonstration, the proposed modeling method was verified by testing.